Immunohistochemical analysis of nm23 gene product/NDP kinase expression in pulmonary adenocarcinoma: lack of prognostic value. - Higashiyama, M. (Nature Publishing Group, 1992)
Levels of nm23 gene product/nucleoside diphosphate kinase (NDP kinase) expression have been demonstrated to correlate inversely with metastatic potential in several tumours, indicating that this could be a useful tool as a prognostic indicator. Using an antibody to NDP kinase, levels of nm23 gene product/NDP kinase expression in pulmonary adenocarcinoma were examined immunohistochemically. Of 88 patients tested, 39 (44%; Group B) showed strong immunoreactivity for NDP kinase in most of cancer cells within the tumour tissues, while 49 (56%; Group A) contained few or no NDP kinase-positive cancer cells. Nm23 gene product/NDP kinase was expressed independently of clinicopathological factors, and unexpectedly, no correlation of survival rates between both Groups could be demonstrated. Thus, in pulmonary adenocarcinoma, levels of nm23 gene product/NDP kinase expression may lack prognostic value. IMAGES: